2009
DOI: 10.29333/ejgm/82649
|View full text |Cite
|
Sign up to set email alerts
|

Serum TNF-Alpha Levels in Acute and Chronic Pancreatitis

Abstract: AimResults: TNF-alpha concentrations were 13. 30±4.42 (7.04-21.35) pg/ml and 9.88±4.68 (3.99-27.73) pg/ml 10.09±1.01 (8.69-14.96) pg/ml in patients with acute and chronic pancreatitis and healthy controls respectively. TNF-alpha concentrations were significantly higher in patients with acute pancreatitis than the patients with chronic pancreatitis. But there was no significant difference between healthy controls and patients with either acute or chronic pancreatitis for TNF-alpha levels. There was no signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…Serum levels of TNF-α have not been considered to be a good indicator of disease severity because the liver is able to rapidly clear TNF-α before it reaches the general circulation; therefore, it is often difficult to detect TNF-α in the serum of acute pancreatitis patients[ 59 ]. One study indicates that TNF-α levels were higher in acute pancreatitis as compared to the chronic form of the disease, but its concentration did not correlate with the severity of disease[ 60 ]. In contrast to this, a recent study has shown levels of TNF-α are also increased in patients with chronic pancreatitis and the concentration of TNF-α coordinately increases in advanced chronic pancreatitis[ 61 ].…”
Section: Tnf-αmentioning
confidence: 99%
“…Serum levels of TNF-α have not been considered to be a good indicator of disease severity because the liver is able to rapidly clear TNF-α before it reaches the general circulation; therefore, it is often difficult to detect TNF-α in the serum of acute pancreatitis patients[ 59 ]. One study indicates that TNF-α levels were higher in acute pancreatitis as compared to the chronic form of the disease, but its concentration did not correlate with the severity of disease[ 60 ]. In contrast to this, a recent study has shown levels of TNF-α are also increased in patients with chronic pancreatitis and the concentration of TNF-α coordinately increases in advanced chronic pancreatitis[ 61 ].…”
Section: Tnf-αmentioning
confidence: 99%
“…Thus, it makes the measurement of TNFα serum level time dependant. 17 Kiyici et al 19 indicates that both acute and chronic pancreatitis show an increase in serum TNFα. A study from Japan also showed that the use of anti-TNFα therapy in AP showed promising results.…”
Section: Discussionmentioning
confidence: 98%
“…However, both the studies signify that the patients with ACP had less severe disease and a lower mortality rate compared to patients with AP without CP [ 18 ]. The AP episodes with underlying CP have reduced levels of cytokines like tumor necrosis factor α leading into less systemic inflammation and organ failure in comparison to AP without underlying CP [ 19 ]. This discrepancy in the severity of attack between ACP and AP without CP can be also explained by the presence of increased fibrosis surrounding the intra-pancreatic fat in CP patients reducing lipolytic flux between acinar cells and adipocytes and also confines the spread of FN and PFAN [ 11 ].…”
Section: Discussionmentioning
confidence: 99%